2020
DOI: 10.1186/s12936-020-3114-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of anti-Plasmodium IgG profiles among Fulani nomadic pastoralists in northern Senegal to assess malaria exposure

Abstract: Background: Northern Senegal is a zone of very low malaria transmission, with an annual incidence of < 5/1000 inhabitants. This area, where the Senegal National Malaria Control Programme has initiated elimination activities, hosts Fulani, nomadic, pastoralists that spend the dry season in the south where malaria incidence is higher (150-450/1000 inhabitants) and return to the north with the first rains. Previous research demonstrated parasite prevalence of < 1% in this Fulani population upon return from the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…Malaria transmission in Senegal is highly seasonal with transmission occurring from July to December, and the main causative agent being P. falciparum [ 12 ]. Recent studies based on serologic data have shown the presence of P. vivax in the region of Matam [ 13 ], and Aedes mosquitoes competent for different dengue serotype transmission have also been isolated in the north [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Malaria transmission in Senegal is highly seasonal with transmission occurring from July to December, and the main causative agent being P. falciparum [ 12 ]. Recent studies based on serologic data have shown the presence of P. vivax in the region of Matam [ 13 ], and Aedes mosquitoes competent for different dengue serotype transmission have also been isolated in the north [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…These patients given their age could have less exposure to the parasite, thus less immunity to GLURP which was shown to be correlated with malaria immunity in different studies [15], [16]. A high seroprevalence of P. falciparum MSP-1 19, CSP and LSA-1 antibodies was observed in the district of Kanel compared to the other districts in the north suggesting frequent exposure to P. falciparum [17]. However, the limited number of samples in this study are insu cient to provide an informative statistical analysis to appreciate the level of immunity in this village.…”
Section: Discussionmentioning
confidence: 84%
“…Senegal is highly seasonal with transmission occurring from July to December, and the main causative agent being P. falciparum [22]. Recent studies based on serologic data have shown the presence of P. vivax in the region of Matam [17], and Aedes mosquitoes competent for different dengue serotype transmission have also been isolated in the north [23].…”
Section: Introductionmentioning
confidence: 99%
“…Our interest in the PF3D7_1035900 protein arose from a survey of the antigen-rich chromosome 10 cluster. A region that contains a number of well-characterized putative vaccine candidates including, the MSP3/6 protein family (18,19), GLURP (20,21), liver stage antigen 1 (22), to name but a few. In addition to its location, transcriptional data demonstrated a peak of expression at the late schizont/early merozoite stage (23,24), a profile that hinted at a biological importance for the late schizont and merozoite stages of the parasite.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this protein family is highlighted by their involvement in fundamental processes essential to parasite biology, including but not restricted to gene regulation and cytokinesis. Essential processes have been linked with the previously described P. falciparum ARM Repeats Only (PfARO) and P. falciparum Merozoite Organizing Proteins (PfMOP) (22), respectively. The putative function of PfARO has been assigned through studies using the Toxoplasma gondii paralog, TgARO (20,21).…”
Section: Introductionmentioning
confidence: 99%